2016
DOI: 10.2147/ijwh.s112226
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward female genital mutilation among Somali and Harari people, Eastern Ethiopia

Abstract: BackgroundFemale genital mutilation (FGM) is a worldwide problem, and it is practiced by many communities in Africa and Asia as well as immigrants from those areas. This practice results in short- and long-term health consequences on women’s health. Like many other developing countries, FGM is widely practiced in Ethiopia, especially among Somali and Harari ethnic groups. Despite intensive campaigns against FGM in Ethiopia, since 2011, it has been practiced in the aforementioned communities. There is no recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 33 publications
7
70
0
Order By: Relevance
“…This nding is supported by other studies conducted in Ethiopia where FGM was spatially clustered with high spot clusters found in Central and East Amhara, North part of SNNP, East Oromia (23). This might be due to different cultural beliefs; in some regions of Ethiopia people believes FGM can reduces sexual hyperactivity, circumcised women are more faithful for their husbands (14,27). Gambela and Tigray regions were cold spots most of the people in this region live in urban areas and being urban residence reduces the chance and support of female genital mutilations (28).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…This nding is supported by other studies conducted in Ethiopia where FGM was spatially clustered with high spot clusters found in Central and East Amhara, North part of SNNP, East Oromia (23). This might be due to different cultural beliefs; in some regions of Ethiopia people believes FGM can reduces sexual hyperactivity, circumcised women are more faithful for their husbands (14,27). Gambela and Tigray regions were cold spots most of the people in this region live in urban areas and being urban residence reduces the chance and support of female genital mutilations (28).…”
Section: Resultssupporting
confidence: 72%
“…With regard to occupation, women who are not currently working had 29 %( AOR=0.71, 95% CI: 0.55, 0.92) less odds of having FGM as compared to their counterpart. A number of studies, however, have reported that women who have occupation/are working had lesser odds of practicing FGM than those who have no occupation (27,33,34). To best of our knowledge, there is no clear justi cation for this nding.…”
Section: Determinant Factors Of Female Genital Mutilation In Ethiopiamentioning
confidence: 89%
See 2 more Smart Citations
“…Also, Ali made references to other stated reasons for FGM such as social pressure, the maintenance of female virginity, hygiene, and economic explanations [3]. Several articles, such as that by Abathun, Sundby and Gele (2012), Berg and Denison (2012), and Isman, Ekéus & Berggrena (2013) describe the attitudes and changing behaviour towards the adoption of a position against this practice [4,5,6], which often becomes evident among immigrants who started to reside in European countries after the FGM and after a process of acculturation. In Europe, women who are at risk or who have already experienced FGM can use this practice as a basis for the so-called cause of asylum.…”
Section: Introductionmentioning
confidence: 99%